Pendampingan penyusunan rencana pembangunan desa berdasarkan SID dan sarana-prasarana: Technical assistance village development base on SID and infrastructure data - Agus Ika Putra; Ari Sandhyavitri; Febrizal Febrizal; Iswadi Hasyim Rosma; Soewignjo Agus Nugroho; Syawal Satibi (IGKOJEI: Jurnal Pengabdian Masyarakat, 2023)
ABSTRACT  As a new administrative region, Teratak Village, Rumbio Jaya, Kampar has not made the best use of the villages' potential for development. The PkM team at Riau University acts as Technical Assistance (TA), providing training and trainers for infrastructure updates and managing SID. The current infrastructure data entry in SID is used to compile RPJM-Des. Primary field data collection surveys were conducted with village officials and Kukerta students. The Teratak Village SID has been completed and is being used as a tool for new data entry in SID usage and management training. The community's aspirations, the village's vision and mission, and development priorities were used as guidelines for the preparation of the RPJM-Des. Training on using SID and simulating new data inputs as scheduled. The municipality, village officials, UMKM and administrators can enter new data and see the potential of the village in SID. RPJM-Des with participatory principles are evidence of good government (participatory, transparent and accountable). The obstacle to the preparation of RPJM-Des is the current information from the APBD district/province to prioritize village development as it must be in-line.  Keywords: Assistance; Development; Information; Infrastructure; Teratak   ABSTRAK Sebagai wilayah administratif baru, Desa Teratak, Rumbio Jaya, Kampar belum memanfaatkan potensi desa yang ada untuk dikembangkan dengan sebaik-baiknya. Tim PkM Universitas Riau berperan sebagai Technical Assistance (TA), memberikan pelatihan dan trainer untuk pemutakhiran infrastruktur dan pengelolaan SID. Entri data infrastruktur yang ada di SID digunakan untuk menyusun RPJM-Des. Survei pengumpulan data lapangan primer dilakukan terhadap aparat desa dan mahasiswa Kukerta. SID Desa Teratak telah selesai dibangun dan digunakan sebagai alat entri data baru dalam pelatihan penggunaan dan pengelolaan SID. Aspirasi masyarakat, visi dan misi desa, serta prioritas pembangunan dijadikan pedoman penyusunan RPJM-Des. Pelatihan penggunaan SID dan simulasi input data baru sesuai jadwal. Pemerintah kota, perangkat desa, UMKM dan pengurus bisa memasukkan data baru dan melihat potensi desa di SID. RPJM-Des dengan prinsip partisipatif merupakan bukti pemerintahan yang baik (partisipatif, transparan dan akuntabel). Kendala penyusunan RPJM-Des adalah informasi terkini dari APBD kabupaten/provinsi untuk memprioritaskan pembangunan desa karena harus sejalan. Kata kunci: Infomasi; Infrastruktur; Pembangunan; Pendampingan; Teratak